ANALISIS SIFAT MEKANIK KARET DARI PENAMBAHAN ASAM GELUGUR SEBAGAI BAHAN PENGGUMPAL LATEKS - Erna Yusniyanti (Universitas Negeri Medan, 2014)
a coagulant. This research aim to know the effect of mixture formic acid and garnicia cambogia to rubber’s mechanical properties according to compound of ASTM 3A. 30% DRC of lateks crumpled with sour mixture of formic acid and granicia cambogia till perfect Iump. treatment of mixing of formic acid and garnicia cambogia was 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%. Then the tested of technical properties is done which is Po and PRI. and then mechanical properties was tested which is Tensile Strength, Elongation at Break, Modulus 300%, Tear Resistance, and Hardness. So for the overall properties tested, formic acid can be substituted for granicia cambogia 20%. where the higher the concentration of granicia cambogia the technical properties, mechanical properties of vulcanized getting smaller. Quality of examinee rubber fulfill SIR standard.